PENGARUH CITRA MEREK, PROMOSI DAN HARGA TERHADAP LOYALITAS KONSUMEN DALAM PEMBELIAN SHAMPOO SUNSILK DI WILAYAH GADEL TANDES SURABAYA - Indah Noviandari, Indah Noviandari (Fakultas Ekonomi Universitas 45 Surabaya, 2019)
Abstract This study aims to determine the effect of brand image, promotion and price on costumer loyalty simultaneously, partialy, and significantly. And to determine which variables have a dominant influence. Methods of research using quantitative methods in the study population are consumers of shampoo Sunsilk in around Gadel Tandes Surabaya. The sampling technique used was simple random sampling with a sample size of 91 respondents to the formula Slovin. Technique uses multiple linier regression analysis. The variable is brand image, promotion, and price on consumer loyalty. Result were obtained value of f count of 29,470 with a significance of 0,000, t value of each, variable of brand image 26.922 > 1.9876, variable of promotion 0.138 < 1.9876, variable of price -0.058 < 1.9876